2022
DOI: 10.14202/vetworld.2022.2929-2936
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and cardiovascular effects of dexmedetomidine premedication and tiletamine-zolazepam for anesthetic induction in dogs

Abstract: Background and Aim: The effect of anesthetic drugs on intraocular pressure (IOP) is an important concern in ophthalmic surgery. The impact of dexmedetomidine (DEX) combined with tiletamine-zolazepam on IOP is scarcely studied. This study aimed to evaluate IOP and cardiovascular effects in dogs after premedication with 5 μg/kg (DEX5) or 10 μg/kg (DEX10) of intramuscular DEX followed by intravenous tiletamine-zolazepam administration for induction of anesthesia in healthy dogs. Materials and Methods: Eighteen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Wolfran et al reported that IM administration of dexmedetomidine (10 μg/kg) reduced IOP and tear production in cats, while a lower dose of 7.5 μg/kg had no significant effect on IOP ( 36 ). In dogs receiving intravenous injection of 5 μg/kg dexmedetomidine, there was no significant difference in IOP measurements within 10 min of drug administration ( 37 , 38 ). Cats sedation with intramuscular 100 μg/kg medetomidine did not cause a statistically significant change in IOP values ( 14 ).…”
Section: Discussionmentioning
confidence: 91%
“…Wolfran et al reported that IM administration of dexmedetomidine (10 μg/kg) reduced IOP and tear production in cats, while a lower dose of 7.5 μg/kg had no significant effect on IOP ( 36 ). In dogs receiving intravenous injection of 5 μg/kg dexmedetomidine, there was no significant difference in IOP measurements within 10 min of drug administration ( 37 , 38 ). Cats sedation with intramuscular 100 μg/kg medetomidine did not cause a statistically significant change in IOP values ( 14 ).…”
Section: Discussionmentioning
confidence: 91%